Evaluasi Sifat-Sifat Kolagen Tulang Broiler pada Penerapan Kombinasi Proses Berbeda (Jurnal Ilmu dan Teknologi Hasil Ternak, 2017)
Collagen is one of the protein derivative products that can be produced by hydrolysis process. Collagen proteins found one of them in bone cattle. The protein is strongly bound to minerals in bone. The process of collagen extraction of bone requires a special method. One of them is demineralization process. The combination of several process methods allows collagen to have different properties. This study aims to evaluate the properties of collagen extract produced from broiler bone in the application of a combination of different processes. The study was used a major sample of composite bone from broiler. The main ingredient is using acetic acid (CH3COOH 1M). The applied treatment was a combination of the use of CH3COOH concentration levels (8%, 10% and 12%) with the length of process (24 and 48 hours)[B1]Â . The data were analyzed by ANOVA using the basic design of Completely Randomized Design (CRD) factorial pattern. Parameters observed included yield, gel strength, viscosity and pH. The results showed that the difference of concentration had significant effect (P<0,05) to pH and viscosity, but no significant effect (P> 0,05) to yield and gel strength. The process length had significant effect (P<0,05) to pH, but to yield, gel strength and viscosity had no significant effect (P>0,05). Application of 10% CH3COOH concentration with a 24 h process length showed better properties in collagen-based composite bone of broiler. Â [B1]Variables measured?